2017
DOI: 10.1111/jcpp.12685
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: The effectiveness of multidimensional family therapy in treating adolescents with multiple behavior problems – a meta‐analysis

Abstract: It can be concluded that MDFT is effective for adolescents with substance abuse, delinquency, and comorbid behavior problems. Subsequently, it is important to match specific characteristics of the adolescents, such as extent of impairment, with MDFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 69 publications
1
39
0
3
Order By: Relevance
“…On the other hand, self-report may invite respondents to also report criminal offences that went unnoticed to police and justice authorities. Database crime records may be more objective, but are often far from complete [ 23 ]. In the studies cited, the effect of treatment on delinquency was assessed from adolescents’ self-report of criminal offences committed, with exception of Dakof et al [ 19 ], who collected crime data from registries to complement the self-reports from the studied participants.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, self-report may invite respondents to also report criminal offences that went unnoticed to police and justice authorities. Database crime records may be more objective, but are often far from complete [ 23 ]. In the studies cited, the effect of treatment on delinquency was assessed from adolescents’ self-report of criminal offences committed, with exception of Dakof et al [ 19 ], who collected crime data from registries to complement the self-reports from the studied participants.…”
Section: Introductionmentioning
confidence: 99%
“…Several independently conducted meta‐analyses (Baldwin, Christian, Berkeljon, & Shadish, ; Tripodi, Bender, Litschge, & Vaughn, ; Van der Pol et al., in press; Vaughn & Howard, ; Waldron & Turner, ) and reviews taking into account study quality (e.g., Becker & Curry, ; Filges, Andersen, & Jorgensen, ) support the capacity of MDFT to significantly reduce youth substance use and a range of other significant problems typically co‐occurring with clinically referred youth. In a review that compared RCT outcomes of five evidence‐supported family‐based therapies for youth substance abuse, Austin, Macgowan, and Wagner () reported large effect sizes (1.28–1.66) for MDFT, as well as comparatively superior outcomes in family functioning and substance use reductions that retained at 1‐year follow‐up.…”
Section: The Mdft Evidence Basementioning
confidence: 99%
“…A consistent outcome of MDFT studies is the program's significant and stable effectiveness with high severity, multiply impaired (comorbidity, see Rowe, ) youth who were clinically referred from diverse treatment settings and sectors of care (mental health, substance abuse, juvenile justice and child welfare) (Hawkins, ; Henderson et al., ; Hendriks, van der Schee, & Blanken, ; Hendriks et al., ; Liddle et al., , in press; Rigter et al., ; Schaub et al., ; see the three‐level meta‐analysis by Van der Pol et al., in press).…”
Section: The Mdft Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…Family-centered approaches were shown to decrease youth recidivism [ 13 , 24 ]. A recent meta-analysis has shown that adolescents with severe behavior problems benefit more from family therapy compared to their peers with less severe behavior problems [ 49 ]. Notwithstanding the evidence, there is a lack of active and positive parental involvement in the juvenile justice system [ 35 ].…”
Section: Introductionmentioning
confidence: 99%